Macrocyclic Complexes of Divalent Transition Metal Ions Derived from 2,2- Dihydroxyindane-1,3-dione and 2,3-/2,6-Diaminopyridines - Singh, D.P.; Mehani Nee Chopra, Rimpi (Asian Journal of Chemistry, 2010)
A new series of divalent iron, cobalt, nickel and copper complexes have been prepared by the condensation of 2,2-dihydroxyindane-1,3-dione and 2,3-/2,6-diaminopyridines. The complexes have been characterized with the help of various physico-chemical techniques like elemental analyses, IR, electronic spectra, conductance and magnetic susceptibi-lities measurements. On the basis of these studies a distorted octahedral geometry has been proposed for all the complexes.